Ecological criteria to identify areas for biodiversity conservation. (September 2017) - Asaad, Irawan; Lundquist, Carolyn J.; Erdmann, Mark V.; Costello, Mark J.
Abstract: A challenge in implementing biodiversity conservation is in reconciling criteria for identifying significant areas and representative networks for biodiversity protection. Many international environmental initiatives include biological, ecological, economic, social and governance criteria to aid selection of areas for biodiversity conservation. Here we reviewed criteria used by 15 international initiatives, and what minimum set of biodiversity variables would be needed to support them. From a range of ecological and biological criteria, we identified eight criteria commonly used to identify areas for biodiversity conservation across these initiatives. Four criteria identified areas that (1) contained unique and rare habitats; (2) included fragile and sensitive habitats; (3) were important for ecological integrity; and (4) were representative of all habitats. Another four criteria were based on species' attributes, including (5) the presence of species of conservation concern; (6) the occurrence of restricted-range species; (7) species richness; and (8) importance for life history stages. Information required to inform these criteria include: habitat cover, species occurrence, species richness, species' geographic range and population abundance. This synthesized set of ecological and biological criteria, and their biodiversity variables will simplify the process to identify additional areas of high biodiversity significance, that in turn support achieving the Convention on Biological Diversity (CBD) targets to fill gaps in the representativeness of the global coverage of protected areas. Highlights: Eight ecological criteria can be used to identify areas for biodiversity conservation. Five biodiversity variables are required to inform the ecological criteria. These biodiversity variables simplify the selection of areas for biodiversity importance.